Academic Status of Plastic Surgery in the United States and the Relevance of Independence - Liu, P.; Singh, M.; Eriksson, E. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2016)
Background: The basic administrative structures at most academic institutions were implemented more than 50 years ago and have remained largely unchanged. Since the surgical specialties were in nascent stages during that time, they were clubbed together within the department of surgery. There has been extensive growth in the breadth and depth of plastic surgery over the past few decades and current administrative structures might not truly reflect the current standing of plastic surgery.Objectives: The goal of this article was to review the academic status of Plastic Surgery in the United States and assess the relevance of independence from the department of surgery.Results: A national survey of 94 hospitals with plastic surgery residency training programs in the United States was conducted to investigate the academic status of plastic surgery. 25 out of those 94 programs had department status with their respective hospitals while another 9 programs were actively planning on transitioning to department status. Out of the 25 plastic surgery hospital departments, 17 programs were also University departments. The number of plastic surgery departments has more than doubled over the past 10 years and continues to rise as more plastic surgery divisions seek department status.Conclusions: There are multiple advantages to seeking department status such as financial and administrative autonomy, ability to participate in medical school curricula, easier access to interdepartmental institutes and faculties, parity with other specialties, and increased control of resident education. There has been concerted advocacy for separating from surgery departments and seeking independent departmental status for plastic surgery. However, the transition from a division to department is a slow and demanding process and requires a well-planned strategy.
Keywords: plastic surgery; academic status; division; department; autonomy